Uma etnografia Virtual sobre imigrantes brasileiros na Irlanda - Lima, Guilherme de (Universidade Federal de São Carlos, 2023)
Ireland has become one of the main migratory routes for Brazilians from all over the country. With a policy of relaxing migration laws, Ireland sounds like a paradise for Brazilians in search of a new life. With a relatively recent history of Brazilian immigration, Ireland is home to a wide variety of immigrant profiles. As a result of the pandemic, the closure of establishments and mass layoffs, many Brazilians found themselves helpless in a new country, with a different culture and language. During the lockdown, there was an increase in the production of digital media on social networks. With this in mind, in this paper we will conduct a virtual ethnography of the production of videos by Brazilian immigrants on YouTube. These videos, with their diverse themes, represent worldviews and valuable migratory stories that are still in progress. In addition, an analysis will be made of the main Irish newspapers on the subject of migration, with a view to identifying Ireland's "official" narratives and their possible concordances and/or discrepancies with the discourse of Brazilian immigrants.
A virtual ethnography about brazilian immigrants in Ireland
Keywords: Imigração brasileira; Irlanda; Netnografia; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA URBANA